Tendon tissue engineering: An overview of biologics to promote tendon healing and repair - Vera Citro; Marta Clerici; Aldo R. Boccaccini; Giovanna Della Porta; Nicola Maffulli; Nicholas R. Forsyth (Journal of Tissue Engineering, 2023)
Tendons are dense connective tissues with a hierarchical polarized structure that respond to and adapt to the transmission of muscle contraction forces to the skeleton, enabling motion and maintaining posture. Tendon injuries, also known as tendinopathies, are becoming more common as populations age and participation in sports/leisure activities increases. The tendon has a poor ability to self-heal and regenerate given its intrinsic, constrained vascular supply and exposure to frequent, severe loading. There is a lack of understanding of the underlying pathophysiology, and it is not surprising that disorder-targeted medicines have only been partially effective at best. Recent tissue engineering approaches have emerged as a potential tool to drive tendon regeneration and healing. In this review, we investigated the physiochemical factors involved in tendon ontogeny and discussed their potential application in vitro to reproduce functional and self-renewing tendon tissue. We sought to understand whether stem cells are capable of forming tendons, how they can be directed towards the tenogenic lineage, and how their growth is regulated and monitored during the entire differentiation path. Finally, we showed recent developments in tendon tissue engineering, specifically the use of mesenchymal stem cells (MSCs), which can differentiate into tendon cells, as well as the potential role of extracellular vesicles (EVs) in tendon regeneration and their potential for use in accelerating the healing response after injury.